Using participatory action learning to Empower the active citizenship of young people. (2nd January 2020) - Jarkiewicz, Anna
ABSTRACT: This article aims to presents the effects of participatory action learning (PAL) as a method of work to Empower the Active Citizenship of young people in schools. The author of the article was involved in an educational project called Future Youth School – Forums (FYS-FORUMS). The basic aim was to create a model of schooling that promotes the idea of active citizenship with the use of a Youth Forum. This study describes the effects of the PAL method on young people in two British schools. The qualitative approach was used to collect data in the study, based on focus group interviews with the youth involved in the project. The impact of the PAL method was identified in a number of areas: (1) the first one concerned the sense of developing the soft/transversal skills and competences; (2) the second one was connected with perceiving oneself as an acting entity; (3) the third one involved improvement of the relationships between students and teachers; and (4) the last effect concerned the evolution of the students' attitude towards active citizenship, which was reflected in their way of thinking about social actions and the need to get involved in them.